Low-dose exposure to PBDE disrupts genomic integrity and innate immunity in mammary tissue - Lamkin, Donald M.; Chen, Shiuan; Bradshaw, Karen P.; Xu, Shili; Faull, Kym F.; Sloan, Erica K.; Cole, Steve W. (Frontiers in Genetics, 2022)
The low-dose mixture hypothesis of carcinogenesis proposes that exposure to an environmental chemical that is not individually oncogenic may nonetheless be capable of enabling carcinogenesis when it acts in concert with other factors. A class of ubiquitous environmental chemicals that are hypothesized to potentially function in this low-dose capacity are synthesized polybrominated diphenyl ethers (PBDEs). PBDEs can affect correlates of carcinogenesis that include genomic instability and inflammation. However, the effect of low-dose PBDE exposure on such correlates in mammary tissue has not been examined. In the present study, low-dose long-term (16 weeks) administration of PBDE to mice modulated transcriptomic indicators of genomic integrity and innate immunity in normal mammary tissue. PBDE increased transcriptome signatures for the Nuclear Factor Erythroid 2 Like 2 (NFE2L2) response to oxidative stress and decreased signatures for non-homologous end joining DNA repair (NHEJ). PBDE also decreased transcriptome signatures for the cyclic GMP-AMP Synthase - Stimulator of Interferon Genes (cGAS-STING) response, decreased indication of Interferon Stimulated Gene Factor 3 (ISGF3) and Nuclear Factor Kappa B (NF-κB) transcription factor activity, and increased digital cytometry estimates of immature dendritic cells (DCs) in mammary tissue. Replication of the PBDE exposure protocol in mice susceptible to mammary carcinogenesis resulted in greater tumor development. The results support the notion that ongoing exposure to low levels of PBDE can disrupt facets of genomic integrity and innate immunity in mammary tissue. Such effects affirm that synthesized PBDEs are a class of environmental chemicals that reasonably fit the low-dose mixture hypothesis.